Remaking history: The pedagogic device and shifting discourses in the South African school history curriculum (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article uses Bernstein’s pedagogic device as a framing heuristic to trace the shifts in the South African school history curriculum from 1995 – 2019. The article focuses on how the instructional and regulative discourses have changed over the past 25 years. The instructional discourse refers to the selection, sequencing, pacing and assessment of knowledge, while the regulative discourse refers to the rules that create social order. I map the curriculum shifts onto the broader policy discourses, such as the competence framework of outcomes-based education (which informed the South African curriculum from 1997 to 2011), the performativity and accountability discourse which emerged after 2012 and the discourses of decolonisation that strengthened after 2015. This article aims to tell the story of how the history curriculum reforms reflect the broader regulative discourses and to show the relationships between the official and pedagogical recontextualising fields. The story is a detailed case study of how curriculum design is influenced by selection logics that are both internal and external to the discipline of history, which reflects curriculummaking as a process fraught with tensions and fractures.
Keywords: School history curriculum; South Africa; Policy discourses; Pedagogic device